2012
DOI: 10.2139/ssrn.2988029
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Toll-Like Receptors in Dendritic Cells of Patients with Dengue During Early and Late Acute Phases of the Disease

Abstract: Background: Dengue hemorrhagic fever (DHF) is observed in individuals that have pre-existing heterotypic dengue antibodies and is associated with increased viral load and high levels of pro-inflammatory cytokines early in infection. Interestingly, a recent study showed that dengue virus infection in the presence of antibodies resulted in poor stimulation of Toll-like receptors (TLRs), thereby facilitating virus particle production, and also suggesting that TLRs may contribute to disease pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
0
13
0
1
Order By: Relevance
“…These events lead to induction of the anti-viral cytokines IFNs, including IFN-b1, IFN-k1, IFN-k2, and IFN-k3, in human DCs. Interestingly, stimulation with the TLR9 ligand CpG A induces less IFN-a expression in peripheral blood mononuclear cells obtained from DENV-infected patients with severe clinical manifestations compared to those with less severe symptoms [24]. This highlights the crucial role of TLR9 signaling in the pathogenesis of DENV infection.…”
Section: Discussionmentioning
confidence: 92%
“…These events lead to induction of the anti-viral cytokines IFNs, including IFN-b1, IFN-k1, IFN-k2, and IFN-k3, in human DCs. Interestingly, stimulation with the TLR9 ligand CpG A induces less IFN-a expression in peripheral blood mononuclear cells obtained from DENV-infected patients with severe clinical manifestations compared to those with less severe symptoms [24]. This highlights the crucial role of TLR9 signaling in the pathogenesis of DENV infection.…”
Section: Discussionmentioning
confidence: 92%
“…Igualmente nosotros reportamos en mDC y pDC obtenidas de pacientes con DF, una mayor expresión de TLR3 y TLR9 en fases tempranas de la infección; por el contrario, en pacientes con manifestaciones graves de la enfermedad se evidenció una disminución en la expresión de TLR3 y TLR9 46 .…”
Section: Papel De Las Células Dendríticas Mieloides (Mdc) Y Células Dunclassified
“…It was recently reported that DENV NS1 proteins may be recognized by TLR2, TLR4, and TLR6 enhancing the production of proinflammatory cytokines and triggering the endothelial permeability that leads to vascular leakage [ 93 , 94 ]. Interestingly, our group has recently shown a differential expression of TLRs in dendritic cells (DCs) of dengue patients depending on the severity of the disease [ 95 ]. Indeed, there was an increased expression of TLR3 and TLR9 in DCs of patients with DF in contrast to a poor stimulation of both receptors in DCs of patients with DHF.…”
Section: Denv and The Immune Responsementioning
confidence: 99%